GAMBARAN PENGETAHUAN REMAJA TENTANG SEKS BEBAS DI SMA MUHAMMADIYAH 01 MEDAN - SITI NUR AFLAH; SAID MUNAZAR RAHMAT (LP2MTBM MAKARIOZ, 2020)
Adolescent is defined as a period of transition between the development of childhood and adulthood, which is accompaniedby changes in the biological, cognitive, and socio emotional. Promiscuous sex is sexual intercourse that is premarital andoften changes partners. The level of adolescent knowledge about sex is the ability of students to understand sex openly andto reduce or prevent the negative effects of sexual behavior. Teenage knowledge about sex in the environment is veryimportant as an alternative that can be taken to improve understanding and sexual behavior of adolescents. This study aimsto determine the knowledge of 10th grade adolescents at Muhammadiyah Senior High School 01 Medan about promiscuoussex. This research uses descriptive method with cross sectional design. The subject of this study was the tenth gradestudents of Muhammadiyah High School 01 Medan. Retrieval of data with total sampling technique, collecting data using aquestionnaire. Data analysis with univariate analysis. Based on the results of univariate analysis, the level of knowledge of10th grade students of Muhammadiyah High School 01 Medan is mostly good, which is 66 respondents (86.8%).The majority of 10th grade adolescents already have a good understanding of promiscuous sex both in each category, aswell as in all categories.